2006
DOI: 10.4489/myco.2006.34.1.022
|View full text |Cite
|
Sign up to set email alerts
|

Production of Gluconic Acid by Some Local Fungi

Abstract: Forty-one fungal species belonging to 15 fungal genera isolated from Egyptian soil and sugar cane waste samples were tested for their capacity of producing acidity and gluconic acid. For the tests, the fungi were grown on glucose substrate and culture filtrates were examined using paper chromatography analysis. Most of the tested fungi have a relative wide potentiality for total acid production in their filtrates. Nearly 51% of them showed their ability of producing gluconic acid. Aspergillus niger was disting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…Czapek-Dox medium has good properties for growth and high biomass production of the most fungi [17,18]. The presence of detergent in the culture medium affects the fungal biomass production according to the type of detergent, fungi species and the applied concentration, due to the influence of detergent on the growth and total dry weight biomass of fungus T. harzianum Rifai investigated in this study, as shown in Figure 1.…”
Section: Resultsmentioning
confidence: 89%
“…Czapek-Dox medium has good properties for growth and high biomass production of the most fungi [17,18]. The presence of detergent in the culture medium affects the fungal biomass production according to the type of detergent, fungi species and the applied concentration, due to the influence of detergent on the growth and total dry weight biomass of fungus T. harzianum Rifai investigated in this study, as shown in Figure 1.…”
Section: Resultsmentioning
confidence: 89%
“…In the presence of d -glucose, some fungi will produce gluconate and its acid form d -gluconic acid as the primary overflow metabolite under non-limiting growth on glucose (Shindia et al. 2006) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the presence of rare 6C sugar acids in meteorites, possibly significant is the relative abundances within this suite: Gluconic acid is not the most abundant (Table 1). A couple of factors, the ubiquitous nature and large relative abundance of glucose and gluconic acid in organisms (i.e., possible sample contaminants) combined with the ability of several microorganisms to oxidize glucose to gluconic acid (15), suggest that gluconic acid would dominate the meteoritic 6C acids if microbial contamination was significant (e.g., Fig. 5A, Lower).…”
Section: Significancementioning
confidence: 99%